Pengaruh Kepemimpinan General Manager Terhadap Disiplin Kerja Karyawan Di Rocky Plaza Hotel Padang - Aisyah Lailana; Hijriantomi Suyuthie (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2020)
This research originated from the observations of researchers when doing the experience of the industrial field in Rocky Plaza Hotel Padang, ehere there are still problems with the work dicipline of employees and the leadership of the general manager. This study aims to determine the effect of general manager leadership on employee work dicipline in Rocky Plaza Hotel Padang This type of research is quantitative with associative causal method. The study population was Rocky Plaza Hotel Padang employees totaling 54 people. The sampling technique in this study uses a non-probability sampling technique, while the type of non-probability used is proportionte stratified random sampling. The data in this study uses primary data for both variables obtained dirctly from employees through a questionnaire compiled based on the likert scale which has been tested for validity an reliability. data analysis technique in this study used regression test with the help of SPSS version 24.00 The results of the study show that: (1) the leadership of the general manager is in the good category of 50%. (2) the work dicipline is in the good category of 50%. (3) the results of the simple linear regression hypothesis test obtained F 15.605 with sig 0,000<0,05. Then the general manager leadership variable can explain the varible work dicipline of employees at 23,1% and 76,9% influenced by other factors. Obtained t value of 3.950 with traf sig 0,000<0,05. Then there is a significant influence between the two variabels. Then obtained a lnear regression coefficient of 0,517 with a sig value of 0,000<0,05 . meaning that every increase in a general manager leadership unit will increase 0.517 work dicipline of Rocky Plaza Hotel Padang.